Hamlet - Mulherin, Jennifer; Payne, Roger, fl. 1969- (Bath, Avon : Cherrytree Books, 1988)
Discusses the plot, characters, and historical background of the Shakespeare play.
Includes index.
Keywords: Shakespeare, William, -- 1564-1616. -- Juvenile literature; Shakespeare, William, -- 1564-1616.; English literature -- History and criticism